AC Line Filter Electrochemical Capacitors: Materials, Morphology, and Configuration. Issue 4 (13th April 2022) - Tang, Haichao; Tian, Yang; Wu, Zhongshuai; Zeng, Yujia; Wang, Yang; Hou, Yang; Ye, Zhizhen; Lu, Jianguo
Abstract : Recently, more and more supercapacitors (SCs) have been developed as AC line filter capacitors, which are generally named AC line filter electrochemical capacitors (FECs). Compared to traditional bulky aluminum electrolytic capacitors (AECs), FECs have higher capacity and lower space occupancy, which makes them a strong competitor. However, different from the common SCs for energy storage, it is necessary to consider the frequency response of the SCs for AC line filtering, where the contradiction between frequency response and specific capacitance is a challenge. The researchers have proposed different solutions from the perspective of materials, morphology, and configuration for this challenge. Based on the above background, in this review, we briefly introduce the principle and parameters of AC line filter electrochemical capacitors. We systematically summarize the state‐of‐the‐art progresses of FECs and discuss their possible application and development in the future. The development of FECs can greatly promote the planarization, integration, and miniaturization of filter capacitors, and provide a new solution for the utilization of green and unstable energy. Abstract : In this review, the filtering mechanism and parameters of AC line filter electrochemical capacitors are introduced, and the progress of FECs in the available literatures is discussed in detail from materials, morphology, configuration, fabrication, and application.